Pengaruh digital marketing dan customer relationship marketing terhadap keputusan pembelian dengan brand image sebagai mediasi (studi pada brand sepatu aerostreet di platform tiktokshop) - Misbahul Anwar; Anantha Jinggar Ramadhani (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
This study aims to analyze the "Influence of Digital Marketing and Customer Relationship Marketing on Purchasing Decisions, with Brand Image as a Mediator (A Study of the Aerostreet Shoe Brand on the TikTokShop Platform)." This quantitative study involved 179 users of the Aerostreet shoe brand on the TikTokShop platform. The sampling technique used a non-probability sampling method with purposive sampling. Data were collected by distributing an online questionnaire. The models analyzed included the outer model, inner model, and hypothesis testing. Calculations using SmartPLS 4.1 revealed that digital marketing has a positive and significant effect on brand image. Customer relationship marketing has a positive and significant effect on brand image. Digital marketing has a positive and significant effect on purchasing decisions. Customer relationship marketing has a positive and significant effect on purchasing decisions. Brand image partially mediates the effect of digital marketing on purchasing decisions. Brand image partially mediates the effect of customer relationship marketing on purchasing decisions